Theoretical Explorations of Structural, Electronic, and Spectroscopic Properties of a Series of Ruthenium Schiff-Base Complexes - G. Sarkar, C. (Journal of Scientific Research, 2023)
The present work concentrates on theoretical investigations of the substituent effects on the reactivity, electronic properties, and UV-vis spectra of a series of ruthenium-Schiff base complexes using density functional theory (DFT). Four complexes are studied herein, where N-(2¢-hydroxyphenyl)benzaldimine is the Schiff base differing in the para-substituent (R) on the benzaldehyde fragment (R = CH3, H, Cl, CF3). B3LYP/SDD-6-31G(d,p) level of theory has been used for computational studies (Gaussian 16). All the structures have been optimized, and the compositions of the frontier molecular orbitals have been analyzed. The energies of HOMO and LUMO and the global indices parameters have been calculated, which reveals that [Ru(PPh3)2(CO)(L-CF3)] is the most reactive complex and [Ru(PPh3)2(CO)(L-Cl)] the least. Time-dependent density functional theory (TDDFT) has been performed to study the electronic absorption parameters. The effect of solvent polarity upon absorption spectra has also been observed. It is found that the lowest energy absorptions in all the complexes show a blue shift with the increase in polarity of the solvent. Natural bond orbital (NBO) analysis of the complexes has been conducted to examine the charge distribution on the donor and the acceptor atoms along with their variation with change in the para-substituent.